How AI is shaping skill demands: insights from an insurance company case study - Umar Baki, Nordahlia; Mohd Rasdi, Roziah (Human Resource Management Academic Research Society, 2024)
This study examines the core competencies needed for AI integration in the insurance industry, focusing on the skill gap that has emerged between employee capabilities and the demands of an AI-driven workplace. Using Crawford’s Integrated Model of Competence as a framework, the study employs a qualitative case study approach—including interviews, focus group discussion (FGD), document analysis, and observations—to explore competencies in an AI-enabled environment. Three main competency areas were identified: knowledge, skills, and abilities, encompassing seven categories such as digital and English language literacy, human-machine collaboration, complex problem-solving, personal management, flexibility, and resilience. The study concluded that critical AI-related skills for insurance professionals, with recommendations for future research to include cross-sectoral studies in Malaysia and longitudinal analyses across different employee levels to track how these competencies adapt and grow with advancing technology